Formation of zircon-type DyCrO4 and its magnetic properties - Ughade, Supriya; Joshi, Bhavana; Poddar, Pankaj (Ceramics International, 2022)
The formation mechanism of hydrolytic sol-gel synthesized DyCrO4 with a complexing agent in acidic and basic mediums is thoroughly studied. The role of complexing agents and pH on phase formation temperature is also intensively investigated. The formation temperature for DyCrO4 is similar to 500 degrees C in the absence and presence of complexing agents such as oxalic acid and ethylenediaminetetraacetic acid (EDTA) at pH 10. When critic acid is used, the DyCrO4 forms with Cr2O3 impurity. The crystallite size in the presence of a complexing agent in the basic medium is similar to 55 nm which is small as compared to only ammonia solution. The various reaction modes lead to tetragonal zircon-type DyCrO4 at similar to 500 degrees C, transforming into orthorhombic perovskite DyCrO3 at 800 degrees C. The magnetization curve shows the ferromagnetic behavior of DyCrO4 below transition temperature T-c similar to 21 K. This low T-c makes nanocrystalline DyCrO4 a potential material for cryogenic applications.
Keywords: Complexing agent; DyCrO4; Formation mechanism; Hydrolytic sol-gel method; pH